2007
DOI: 10.1590/s0102-71822007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Maconha e contexto familiar: um estudo psicossocial entre universitários do Rio de Janeiro

Abstract: RESUMO: O objetivo deste trabalho foi estudar o contexto familiar de usuários e não-usuários de maconha. Adotamos a teoria das representações sociais de Moscovici (1961Moscovici ( /1976Moscovici ( , 1988, além de algumas reflexões de Becker (1971) e Foucault (1977, 1997. Participaram da pesquisa sessenta universitários do Rio de Janeiro, de ambos os sexos, entre 17 e 30 anos. Utilizamos um questionário com perguntas abertas, no qual eles apresentaram seus familiares. O material obtido foi analisado em termos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The families of non-users, in turn, held links with less authority that favored interpersonal connections marked by relations of exchange and fellowship. 30 Regarding the use of alcohol and other drugs, a study among undergraduate students of courses in the fields of biological, exact, and human sciences evidenced an association of family aspects with regular use of drugs. 31 When it comes to spirituality, other studies have found no significance between spirituality and drug consumption.…”
mentioning
confidence: 99%
“…The families of non-users, in turn, held links with less authority that favored interpersonal connections marked by relations of exchange and fellowship. 30 Regarding the use of alcohol and other drugs, a study among undergraduate students of courses in the fields of biological, exact, and human sciences evidenced an association of family aspects with regular use of drugs. 31 When it comes to spirituality, other studies have found no significance between spirituality and drug consumption.…”
mentioning
confidence: 99%